Learner Characteristics to Form Character Development and Skills in Positive Habits - Pangesti, Atira Diyah; Fithrotuzzahra, Kamila; Sri Untari, Rahmania (Procedia of Social Sciences and Humanities, 2024)
The research aims to determine the practice of positive habits in regulating student characteristics to form good character development and skills. The research method used is a qualitative research method with a descriptive approach. The results of this research are that positive habit formation activities have a significant impact on the formation of student characteristics. The results of this research support various theories in learning and developmental psychology which show that behavior and personality can be shaped through consistent practice and reinforcement. By carrying out systematic and sustainable positive habit formation activities, schools can help students develop positive characters that are important for academic success and everyday life. The implication of these findings is that schools and educators need to be committed to creating an environment that supports student character development through various well-designed programs and activities.